Efektivitas Model Pembelajaran Role Playing Dalam Meningkatkan Aktivitas Belajar Siswa Pada Kurikulum Merdeka - Yogi Nurfauzi; Risnawati Risnawati; Dina Mayadiana Suwarna; Ali Ramatni; Joni Wilson Sitopu; Janes Sinaga (Journal on Education, 2023)
Based on the results of observations at SMP Negeri 29 Tangerang, it is necessary to have meaningful learning that is able to involve students in all the activities carried out in the learning. The role playing model is an alternative in the successful implementation of the independent curriculum. Besides that, the low student learning outcomes in learning and student learning activities need to be activated, this can be seen from the completeness of student learning which only reaches less than 50% and many student scores are below the KKM. role playing models in learning. This research is a Classroom Action Research (PTK) which consists of Pre-cycle, Cycle I, Cycle II and Cycle III. Each cycle ends with an evaluation. Each cycle consists of planning, implementation, evaluation and reflection. Based on the results of the research that has been carried out then the findings are analyzed in the field so that it can be concluded that the use of the role playing model in increasing student learning activities for the development of an independent curriculum can increase student learning activities at SMP Negeri 29 Tangerang.